GANTI RUGI AKIBAT PEMBATALAN KHITBAH DALAM PERSPEKTIF HUKUM ISLAM ; STUDI KASUS PEMBATALAN KHITBAH DI KOTA MEDAN - Uswatun Hasanah (IAIN Padangsidimpuan, 2022)
Compensation due to cancellation of sermons according to article 13 of the KHI (Islamic Jurisprudence) does not give impact in legal consequences. However, Islamic law has an opinion that allows for compensation due to the cancellation of the Khitbah (requests) in line with the opinion of Dr. Muhammad Abu Zahrah. And the compensation is also for the benefit of people so that none of the parties feel wronged since of the suffering they feel as a result of the cancellation.